2019
DOI: 10.1111/jfb.13904
|View full text |Cite
|
Sign up to set email alerts
|

Measuring cortisol, the major stress hormone in fishes

Abstract: Stress in teleosts is an increasingly studied topic because of its interaction with growth, reproduction, immune system and ultimately fitness of the animal. Whether it is for evaluating welfare in aquaculture, adaptive capacities in fish ecology, or to investigate effects of human‐induced rapid environmental change, new experimental methods to describe stress physiology in captive or wild fish have flourished. Cortisol has proven to be a reliable indicator of stress and is considered the major stress hormone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(174 citation statements)
references
References 132 publications
(203 reference statements)
3
141
0
Order By: Relevance
“…Cortisol level in plasma is a well-accepted acute stress indicator, and has been successfully applied to assess a level of stress both in the controlled environments and in the wild (reviewed by Sadoul and Geffroy [52]). Expression of cr in A. brama from the exposed population in our study is not significantly different from the reference population, indicating low level of acute stress in the fish.…”
Section: Adaptive Responses In a Brama Exposed To Chemical Stressmentioning
confidence: 99%
“…Cortisol level in plasma is a well-accepted acute stress indicator, and has been successfully applied to assess a level of stress both in the controlled environments and in the wild (reviewed by Sadoul and Geffroy [52]). Expression of cr in A. brama from the exposed population in our study is not significantly different from the reference population, indicating low level of acute stress in the fish.…”
Section: Adaptive Responses In a Brama Exposed To Chemical Stressmentioning
confidence: 99%
“…Traditionally, measurements of circulating levels of plasma cortisol from whole body-or blood sampling have been used as a proxy for measuring stress in fish, but this method requires the invasive collection of blood or tissue 29 . Novel alternative techniques are available and have been shown to provide robust data on cortisol levels, ranging from non-invasive sampling of faeces, urine or water-borne cortisol to more invasive sampling of fin tissue, mucous or scales 30,31 . However, all of these techniques require the collection of blood, water or tissue and will consequently only provide a "snapshot" of the recovery period or level of stress.…”
mentioning
confidence: 99%
“…With respect to SPE format, the original report of this technique employed Sep Pak C18 cartridges (Ellis et al, 2004) and this format remains widely used Ellis et al, 2013;Fanouraki et al, 2008;Newman et al, 2015;Sadoul & Geffroy, 2019;Wong et al, 2008). We found that the recoveries of known amounts of cortisol from acidified water samples were reasonably high using this SPE format.…”
Section: Non-invasive Cortisol Determinationmentioning
confidence: 58%
“…As the principal glucocorticoid in teleosts, cortisol is a marker of the primary stress response (Barton, 2002;Sopinka et al, 2016;Sadoul & Geffroy, 2019). In order to obtain multiple measurements on the same fish with minimal disturbance, we monitored cortisol noninvasively by measuring its release from the fish into the surrounding water (Ellis et al, 2013;.…”
Section: Introductionmentioning
confidence: 99%